EFFECTIVENESS OF VIDEO-BASED MICROLEARNING IN ENHANCING STUDENTS’ LEARNING OUTCOMES ON THE CONCEPT OF HUMAN COORDINATION SYSTEM - Eka Lestari; Ismail Ismail; Nurhayati B (JURNAL PENA SAINS, 2026)
This study aims to determine the effectiveness of the use of microlearning video coordination system in improving the learning outcomes of grade XI students of SMA Negeri 2 Makassar. This study used a pre-experimental design method with a One Group Pretest-Posttest design. The research sample consisted of 30 grade XI Biology 1 students selected using a purposive sampling technique. The research instrument used was a multiple-choice learning outcome test consisting of 15 questions given before learning (pretest) and after learning (posttest). The research data were analyzed using descriptive statistical analysis and the N-Gain test to determine the improvement in student learning outcomes after the implementation of microlearning videos. The results showed that there was an increase in student learning outcomes after the implementation of microlearning videos. The average pretest score of 49.77 increased to 79.77 in the posttest. In addition, the results of the N-Gain analysis obtained an average of 60.83 which is in the moderate or quite effective category. Most students are in the quite effective category with a percentage of 63.43%, while 3.33% are in the effective category. These results indicate that the use of microlearning videos has a positive impact on improving student learning outcomes in the coordination system material. Therefore, microlearning videos can be used as an alternative, engaging, flexible, and effective learning medium in biology learning.